2018
DOI: 10.3390/ijerph15081786
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Using Public Health Impact Criteria to Develop Environmental Health Indicators: The Example of the Indoor Environment in New Zealand

Abstract: Developing environmental health indicators is challenging and applying a conceptual framework and indicator selection criteria may not be sufficient to prioritise potential indicators to monitor. This study developed a new approach for prioritising potential environmental health indicators, using the example of the indoor environment for New Zealand. A three-stage process of scoping, selection, and design was implemented. A set of potential indicators (including 4 exposure indicators and 20 health indicators) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…A robust and well-tested process for developing indicators was used. This indicator development process was adapted from methods for developing environmental health indicators [ 52 ], based on the World Health Organization’s process for developing children’s environmental health indicators [ 53 ] and Statistics New Zealand guidance for developing indicators [ 54 ]. Methods for developing environmental health indicators are relevant for this work, given their focus on the impacts of environmental hazards on human health and wellbeing, and the social, economic and demographic context in which these impacts occur.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A robust and well-tested process for developing indicators was used. This indicator development process was adapted from methods for developing environmental health indicators [ 52 ], based on the World Health Organization’s process for developing children’s environmental health indicators [ 53 ] and Statistics New Zealand guidance for developing indicators [ 54 ]. Methods for developing environmental health indicators are relevant for this work, given their focus on the impacts of environmental hazards on human health and wellbeing, and the social, economic and demographic context in which these impacts occur.…”
Section: Methodsmentioning
confidence: 99%
“…A public health perspective was incorporated in the indicator selection process, with indicators focusing primarily on those indicators relevant to the potential impacts on people’s health and wellbeing. The indicators were then evaluated against ten indicator selection criteria, based on previous statistical guides [ 54 ] and the EHINZ programme [ 52 ], and adapted to meet the specific needs of the end users ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Ingham et al (2019) described housing as a risk factor for childhood respiratory illness and found a dose response association between housing quality, measured related to damp and mould, and hospital admission for young children. Mason, Lindberg, Read and Borman (2018) also found that damp, mouldy housing had a major effect on children's health in their Aotearoa New Zealand study, with approximately 500 children admitted to hospital annually due to asthma.…”
Section: Poor Quality Housingmentioning
confidence: 96%
“…Nevertheless, using this type of evidence to inform the design and evaluation of policies in urban settings is an under-researched area [ 20 ]. Mason and Lindberg [ 21 ] and Pine and Glonti [ 22 ] reported that researchers and policymakers value data and expertise in the local context. The literature also recalls that built and natural environment indicators must have a proven effect on health and that their selection should be based on a sound approach, so that they can become a resource in identifying potential risks to health [ 23 ].…”
Section: Introductionmentioning
confidence: 99%